Reinforced bioplastic film at different microcrystalline cellulose concentration - Nor Amira, Othman; Fatmawati, Adam; Nur Hidayah, Mat Yasin (Elsevier Ltd, 2021)
Plastic pollution has led to the development of bioplastic to replace conventional petroleum-based plastic. It has received attention and interest from many researchers due to the global issues of plastic pollution. The formulation to synthesize the bioplastic film has been established throughout the years with the incorporation of renewable sources such as starch, cellulose, plasticizer and several other additives to obtain a high quality bioplastic film. This study formulated a biocomposite using carrageenan, microcrystalline cellulose (MCC), polyethylene glycol (PEG), glyoxylic acid and hydroxypropyl methylcellulose (HPMC) to produce bioplastic films reinforced from a renewable resource. The percentage of MCC was manipulated through the study to observe the strength of the film obtained with the increasing percentage of MCC. The film was cast onto the stainless steel plate and left to dry for 3 h at 60 °C. The results demonstrated that the highest value of tensile strength is 20.74 MPa at 1% of MCC addition. Besides that, the value of moisture content increased with the increasing percentage of MCC which is 16.72% at 3.5% of MCC concentration. Results showed that the increasing concentration of MCC increased the moisture content in the film hence influenced the strength of the bioplastic film obtained.